THE CLINICAL EFFECT OF ORAL VITAMIN D₃ SUPPLEMENTATION ON PSORIASIS PATIENTS ATTENDING OUTPATIENT TERTIARY CARE CENTRE - Dr Surendra Singh Bhati; Dr Ujjwal Jharia; Dr Shelly Yadav; Dr Ayush Yadav (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Psoriasis is a chronic immune-mediated inflammatory skin disease characterized by hyperproliferation of keratinocytes and dysregulated immune responses. Emerging evidence suggests a link between vitamin D deficiency and increased disease severity in psoriasis due to its role in epidermal homeostasis and immune modulation. However, the therapeutic efficacy of oral vitamin D₃ supplementation in Indian patients with chronic plaque-type psoriasis remains underexplored. The present study aimed to evaluate the clinical efficacy and safety of oral vitamin D₃ supplementation in patients with chronic plaque psoriasis and low baseline serum vitamin D levels. Methods: This prospective interventional study included 100 adult patients with chronic plaque-type psoriasis and documented serum 25(OH)D levels <30 ng/mL. Participants received oral vitamin D₃ (60,000 IU weekly) for 6 months, without systemic antipsoriatic therapy. Clinical severity was assessed using the Psoriasis Area and Severity Index (PASI), while serum vitamin D levels were monitored at baseline, 3 months, and 6 months. Statistical analyses included paired t-tests, ANOVA, Pearson correlation, and independent samples t-tests. Results: Mean serum vitamin D levels increased from 17.42 ng/mL to 40.85 ng/mL over 6 months (p<0.001), while mean PASI scores declined from 8.84 to 3.69 (p<0.001), demonstrating significant clinical improvement. A moderate, statistically significant inverse correlation (r = –0.527, p<0.01) was found between vitamin D levels and PASI scores. Improvement was comparable across age groups, skin types (Fitzpatrick III vs IV, p=0.691), and baseline PASI severity (p=0.091). Patients with severe baseline disease showed the greatest mean improvement (65.8%). No serious adverse events were reported, with mild side effects (nausea, constipation) noted in 28% of patients. Conclusion: Oral vitamin D₃ supplementation is a safe, effective, and well-tolerated adjunctive treatment for chronic plaque psoriasis, demonstrating consistent clinical benefit irrespective of age, skin type, or baseline disease severity. These findings support routine screening for vitamin D deficiency in psoriasis and its correction as part of comprehensive management. Further large-scale, randomized studies are recommended to validate these results and explore combinatory therapeutic approaches.